Hot Water Supply Test Using Geothermal Heat Pump Systems at Petropavlovsk-Kamchatsky, The Capital of Kamchatka, Russia - Ikeuchi, Ken (Geo-Heat Center, Oregon Institiute of Technology, Klamath Falls, OR (USA), 2001)
“Fundamental investigation of the promotion of a joint implementation for the fiscal year 1998 - The fundamental investigation related to local heating utilizing geothermal in Kamchatka, Russia” was carried out with the support of the New Energy and Industrial Technology Development Organization (NEDO). It was carried out as a feasibility study and to implement the “joint implementation.” As the results, it was verified that heating by geothermal heat pump (GHP) can be used instead of the existing boiler heating in the severe climate condition in Kamchatka. In this report, the results of the GHP test as a part of this feasibility study is summarized